Analisis Kadar Trigliserida pada Konsumen Minuman Kopi Modern di Kota Bengkulu - Putri Widelia Welkriana; Melda Wulan Dari (Poltekkes Kemenkes Bengkulu, 2026)
Coffee consumption has become a lifestyle in Bengkulu City. Contemporary coffee is served with added sugar, milk, or syrup, which may affect blood lipid levels. High triglyceride levels indicate fat metabolism disorders and risk of atherosclerosis. Objective: To describe triglyceride levels among contemporary coffee consumers at coffee shops in Bengkulu City, 2025. Method: Descriptive analytical research with convenience sampling on 40 respondents. Data collected via interviews and laboratory examinations. Results: Respondents were mostly female (57.5%), aged 18–25 years (mean 20.3 years), 92.5% consumed coffee for < 2 years. Most respondents (95.0%) had normal triglyceride levels, while 5.0% were abnormal. Conclusion: Triglyceride levels are mostly normal. Limiting consumption is recommended.